MANAJEMEN PRIVASI KOMUNIKASI DALAM MELINDUNGI DIRI DI TWITTER (X) (Studi Kasus Remaja Kasus Cyberbullying) - Kardiyanti, Inma Dwi Putri; Bahfiarti, Tuti; Muh. Akbar (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2024)
This study aims to analyze the communication privacy management employed by adolescents who have experienced cyberbullying to protect themselves on Twitter (X). The theoretical framework used is Communication Privacy Management with a focus on interpersonal communication concepts. The research method applied in this thesis is qualitative, using a phenomenological approach. The study was conducted online. Primary data were collected through in-depth interviews with informants and observations of their Twitter (X) accounts, while secondary data were gathered from books, journals, articles, and websites. Informants were selected using purposive sampling, consisting of four adolescents who were victims of cyberbullying on Twitter (X). The data were analyzed using the Miles and Huberman data analysis method. This research analyzes the application of communication privacy management among adolescents who are victims of cyberbullying, using five key principles: (a) ownership of private information, (b) control of private information, (c) privacy rules, (d) shared ownership and guardianship of private information, and (e) boundary turbulence of private information. The results of this study indicate that out of the five principles of communication privacy management, two principles are more frequently utilized by adolescents to manage their communication privacy and protect themselves on Twitter (X): Control of Private Information and Privacy Rules, through actions such as locking their accounts, disabling Direct Message (DM) access, and limiting comments on their posts. Keywords: Communication Privacy Management; Cyberbullying; Adolescent; Twitter (X)